Why do we need a Global Program to Tackle Climate Change? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Thomas Rosswall, CCAFS SC Chair. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya